ZIRCON PARAGENESES IN MIGMATITES OF THE PRE-RIPHEAN CRYSTALLINE BASEMENT OF THE SIKHOTE ALIN - Levashev G.B.; Semenova N.N.; Sapin V.I. (My University, 1989)
Microprobe study of zircon parageneses in migmatites of different origin shows that the geochemical properties of zircon could be used to solve important petrological and geochemical problems. The standards employed for this purpose were genetically different igneous rock types, characteristic of the crystalline basement of the Sikhote Alin folded region, represented by migmatite-granite, migmatite-plagio-granite and metamafic associations. No zircon parageneses confirming the possibility that the granitic crust of the Sikhote Alin fold system was formed at the expense of its metamafic basement rocks have yet been found in real geologic situations. It is more likely that the substrate consisted of crystalline schists and gneisses of old greenstone belts, which served as the common matrix of rocks of migmatite-granite and migmatite-plagio-granite associations.
Keywords: Riphean; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей